1990
DOI: 10.1203/00006450-199001000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Taurine and Osmoregulation. III. Taurine Deficiency Protects against Cerebral Edema during Acute Hyponatremia

Abstract: ABSTRACT. Taurine is a cerebral osmoprotective molecule during chronic hypernatremic dehydration. In these experiments, we investigated the role of taurine in osmoregulation during acute hyponatremia. Taurine deficiency was induced in experimental cats (n = 6) by feeding a taurine-free diet for 8-10 wk, whereas control counterparts (n = 6) consumed a regular diet. Hyponatremia was provoked in all cats over 54 h by daily injections of 5% dextrose in water (7.5% body wt) and vasopressin (20 U/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Taurine deficiency in experimental cats was protective against CE during acute hyponatremia [35], implicated as a risk factor in the pathogenesis of DKA associated CE [36]. Our demonstration of rapid, but incomplete, extrusion of taurine under such conditions supports these findings.…”
Section: Discussionsupporting
confidence: 81%
“…Taurine deficiency in experimental cats was protective against CE during acute hyponatremia [35], implicated as a risk factor in the pathogenesis of DKA associated CE [36]. Our demonstration of rapid, but incomplete, extrusion of taurine under such conditions supports these findings.…”
Section: Discussionsupporting
confidence: 81%
“…However, changes in the number of osmotically active particles do not necessarily reflect the volume regulating capacity of the brain. For instance, Trachtman et al (1990) reported that an average decrease in taurine by as little as 1.5 m M in the brains of taurinedeficient kittens significantly protects against hypoos-motic cerebral edema. The fact that brain electrolytes, the quantitatively most important osmolytes, are not different between hypoosmotic taurine-supplemented and -deficient kittens (Trachtman et al, 1990) supports the contention above.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, intravenous administration of mannitol has been found to reduce cellular edema, minimize swelling-induced disruption of the cell membrane and eliminate the no-reflow phenomenon in the ischemic myocardium. Similarly, a reduction in the intracellular osmotic load through taurine depletion reduces cerebral edema during acute hyponatremia 4 and protects the heart against ischemia 5 • Thus, the acute effects of taurine loss can significantly benefit the osmotically stressed cell.…”
Section: Osmoregulation As a Cytoprotective Mechanismmentioning
confidence: 99%